(untitled) - Hanrahan, Grady (Waltham, MA, 2012)
Offers an introduction to environmental chemistry principles and the dynamic nature of environmental systems. This title provides integrated tools in explaining complex chemical problems of environmental importance.
Keywords: Environmental chemistry,Hóa học môi trường